Choice of Vitrification Mode for Macroporous Matrices Seeded with Mesenchymal Stromal Cells - Trufanova , Natalia; Kovalenko , Igor; Petrenko, Oleksandr (Problems of Cryobiology and Cryomedicine, 2020)
The composition of the solution of cryoprotectants and vitrification conditions (saturation methods, removal of cryoprotectants, cooling-warming modes) of tissue engineered constructs based on macroporous matrices (MPM) and mesenchymal stromal cells (MSCs), preventing the development of crystallization and cracking of a glassy phase, were determined and the influence of the developed conditions on cell viability and MPM structure was studied. Crystallization and cracking were investigated during MPM cooling and warming in cryoprotectant solutions in cryovials. The viability of MSCs in suspension was determined by trypan blue staining, and that as a part of MPM was examined by ethidium bromide and fluorescein diacetate staining. The MSCs metabolic activity was evaluated with the MTT test. The selected conditions were shown to provide a high viability of MSCs after vitrification in the form of a suspension, but required an improvement to preserve the cells seeded in macroporous matrices. Probl Cryobiol Cryomed 2020; 30(1): 77-89